Investigating the Integrated Leader Member Exchange and Supply Chain Strategy on Employee Performance - Moses Glorino Rumambo Pandin; Mohamad Iqbal Arrasyid; Amaliyah Amaliyah (International Journal of Supply Chain Management, 2019)
This paper examines the relationship between employee commitment and supply chain integration dimensions by Leader-Member Exchange (LMX) to explain several performance measures, such as flexibility, delivery, quality, inventory and customer satisfaction. So three elements shape leadership in Leader-Member Exchange (LMX) theory as a relationship and process are investigated. LMX quality is important for the company, because it relates to employee behavior and attitudes, including improving employee performance. The research method applied literature review using description logic and systematics. In this article the theory will be observed specially the effect of LMX on employee performance and antecedents of LMX. The results of the study found that the effect of LMX quality on performance is determined by the characteristics of the task as antecedent LMX in the company.